Correction: A flexible, multifunctional, active terahertz modulator with an ultra-low triggering threshold. Issue 30 (23rd July 2020) - Ma, He; Wang, Yu; Rong, Lu; Tan, Fangrui; Fu, Yulan; Wang, Guang; Wang, Dayong; Liu, Kai; Fan, Shoushan; Jiang, Kaili; Zhang, Xinping
Abstract : Correction for 'A flexible, multifunctional, active terahertz modulator with an ultra-low triggering threshold' by He Ma et al., J. Mater. Chem. C, 2020, DOI: ; 10.1039/d0tc02446e .